The Effectiveness of the Role of BPJS Kesehatan in Supporting Access to Mental Health Services in Puskesmas as a Primary Service in Indonesia: A Literature Review - Mewani Sinaga; Mutiara Salsabila; Fitriani Gurning (Sean Institute, 2025)
Mental health is an important part of public health that requires special attention, especially in the context of primary services such as health centers. This study aims to evaluate the effectiveness of the role of BPJS Kesehatan in improving access to mental health services in Indonesia through a systematic literature review of selected articles from electronic databases (Google Scholar, PubMed, SpringerLink). The results of the study show that BPJS plays an important role in expanding access and reducing treatment costs by up to 50%, as well as supporting the successful rehabilitation of patients with mental disorders by 60%. However, challenges still arise from the lack of professionals, the length of waiting time, to the limited understanding of participants regarding the scope of services. Therefore, improvements are needed in the aspects of cost management, capacity building of health workers, strengthening coordination between agencies, and socialization to the community. These findings provide important input for efforts to optimize the national health social security system in facing the challenges of mental health services.